Gut microbiota of white-headed black langurs (Trachypithecus leucocephalus) in responses to habitat fragmentation - Lai, Ying; Chen, Yanqiong; Zheng, Jingjin; Liu, Zheng; Nong, Dengpan; Liang, Jipeng; Li, Youbang; Huang, Zhonghao (Frontiers in Microbiology, 2023)
The white-headed black langur (Trachypithecus leucocephalus) is exclusively distributed in the karst forests and is critically endangered owing to habitat fragmentation. Gut microbiota can provide physiological data for a comprehensive study of the langur’s response to human disturbance in the limestone forest; to date, data on spatial variations in the langurs’ gut microbiota are limited. In this study, we examined intersite variations in the gut microbiota of white-headed black langurs in the Guangxi Chongzuo White-headed Langur National Nature Reserve, China. Our results showed that langurs in the Bapen area with a better habitat had higher gut microbiota diversity.In the Bapen group, the Bacteroidetes (13.65% ± 9.73% vs. 4.75% ± 4.70%) and its representative family, Prevotellaceae, were significantly enriched. In the Banli group, higher relative abundance of Firmicutes (86.30% ± 8.60% vs. 78.85% ± 10.35%) than the Bapen group was observed. Oscillospiraceae (16.93% ± 5.39% vs. 16.13% ± 3.16%), Christensenellaceae (15.80% ± 4.59% vs. 11.61% ± 3.60%), and norank_o__Clostridia_UCG-014 (17.43% ± 6.64% vs. 9.78% ± 3.83%) (which belong to Firmicutes) were increased in comparison with the Bapen group. These inter-site variations in microbiota diversity and composition could be accounted for by differences in food resources caused by fragmentation. Furthermore, compared with the Banli group, the community assembly of gut microbiota in the Bapen group was influenced by more deterministic factors and had a higher migration rate, but the difference between the two groups was not significant. This might be attributed to the serious fragmentation of the habitats for both groups. Our findings highlight the importance of gut microbiota response for the integrity of wildlife habitats and the need in using physiological indicators to study the mechanisms by which wildlife responds to human disturbances or ecological variations.